Fatigue in type 1 diabetes, prevalence, predictors and comparison with the background population. (September 2018) - Jensen, Øystein; Bernklev, Tomm; Gibbs, Charlotte; Moe, Ragnar Bekkhus; Hofsø, Dag; Jelsness-Jørgensen, Lars-Petter
Highlights: Fatigue is more common in type 1 diabetes than in the background population. Anxiety, depression and sleep problems displayed the highest association with fatigue. The Fatigue Questionnaire displayed satisfactory psychometric properties. Abstract: Aim: Fatigue is scarcely studied in type 1 diabetes (T1D), and the aims were to investigate its prevalence compared to the background population, potential associations, and to validate the Fatigue Questionnaire (FQ) in type 1 diabetes. Methods: Persons with T1D were recruited from three outpatient clinics in Norway. Fatigue was measured using the FQ, and FQ data from the Norwegian background population were used for comparison. Socio-demographic and clinical variables were obtained by self-report, clinical investigation, medical records and laboratory tests. Results: Of 332 eligible patients, 288 (87%) were included. Mean age was 44.65/44.95 years (SD 13.34/13.38) for females/males, respectively. Total fatigue (TF) was 15.31 (SD 5.51) compared to 12.2 (SD 4.0) in the background population ( p < 0.001). HADS ≥ 8, current menstruation, increased leukocytes and sleep problems were associated with increased TF. Chronic fatigue (CF) was reported in 26.4% compared to 11% in the background population (p < 0.001). HADS ≥ 8, increased time since diagnosis and decreased sleep quality were associated with CF. The validity, internal consistency and repeatability of the FQ was confirmed. Conclusions: Fatigue was more common in T1D than in the background population, and associated with increased anxiety, depression and sleep problems. The FQ demonstrated satisfactory psychometric properties.